An Endoplasmic Reticulum (ER) Membrane Complex Composed of SPFH1 and SPFH2 Mediates the ER-associated Degradation of Inositol 1,4,5-Trisphosphate Receptors - Pearce, Margaret M. P. (American Society for Biochemistry and Molecular Biology, 2009)
How endoplasmic reticulum (ER) proteins that are substrates for the ER-associated degradation (ERAD) pathway are recognized for polyubiquitination and proteasomal degradation is largely unresolved. Inositol 1,4,5-trisphosphate receptors (IP(3)Rs) form tetrameric calcium channels in ER membranes, whose primary role is to control the release of ER calcium stores, but whose levels are also regulated, in an activation-dependent manner, by the ERAD pathway. Here we report that the ER membrane protein SPFH1 and its homolog SPFH2 form a heteromeric ∼2 MDa complex that binds to IP(3)R tetramers immediately after their activation and is required for their processing. The complex is ring-shaped (diameter ∼250Å(),) and RNA interference-mediated depletion of SPFH1 and SPFH2 blocks IP(3)R polyubiquitination and degradation. We propose that this novel SPFH1/2 complex is a recognition factor that targets IP(3)Rs and perhaps other substrates for ERAD.